Strategi Pertahanan Semesta: Memahami Green and Blue Belt Security dalam Konsep Ekonomi Konstitusi di Kawasan Perbatasan - Syarifuddin Tippe (SISI LAIN REALITA, 2016)
The concept of green and blue belt security in the framework of the concept of constitutional economy is derived from solving the root of the nation's problems with transdisciplinary methods. That is, this concept is understood as an integral part of the awareness efforts for the state organizers to consistently adhere to the ideological base of Pancasila in the nation and state. On that understanding, the understanding of the framework of the concept of constitutional economy must be put forward than the concept of green and blue belt security itself. Concretely, it must follow a comprehensive flow of understanding in accordance with the structure of the problem. The earliest is the understanding of root-breaking problems related to consistency with the ideological base of Pancasila (this has already been discussed); The next understanding of the "problem stem" is "state / government policy" which can be interpreted as the basis of work with the term "constitutional economy". While the understanding associated with kosep green and blue belt security is an understanding of "state defense strategy" in the border region.